Cost-effectiveness of neck-specific exercise with or without a behavioral approach versus physical activity prescription in the treatment of chronic whiplash-associated disorders: Analyses of a randomized clinical trial. Issue 25 (June 2017) - Landén Ludvigsson, Maria; Peolsson, Anneli; Peterson, Gunnel; Dedering, Åsa; Johansson, Gun; Bernfort, Lars
Abstract: Background: Fifty percent of people injured by whiplash still report neck pain after 1 year and costs associated with whiplash associated disorders (WAD) are mostly attributed to health service and sick-leave costs in chronic conditions. With increasing health care expenditures the economic impact of interventions needs to be considered. Objective: To analyze the cost-effectiveness of physiotherapist-led neck-specific exercise without (NSE) or with a behavioral approach (NSEB), or prescription of physical activity (PPA) in chronic WAD, grade 2 to 3. Methods: This is a secondary cost-effectiveness analysis of a multicenter randomized clinical trial of 216 participants with chronic WAD grade 2 to 3. The interventions were physiotherapist-led neck-specific exercise without or with a behavioral approach, or prescription of physical activity for 12 weeks. Incremental cost-effectiveness ratios (ICERs) were determined after 1 year and bootstrapped cost-effectiveness planes and sensitivity analyses of physiotherapy visits were performed. Health care and production loss costs were included and quality-adjusted life years (QALYs) were estimated, using the Euroqol-5D questionnaire. Comparisons with the Short Form-6D, and neck disability index (NDI) were also made. Results: The 1-year follow-up was completed by 170 participants (79%). Both physiotherapist-led groups improved in health related quality of life. The intervention cost alone, per quality-adjusted life year (QALY) gain in the NSE group was US$ 12, 067. A trend for higher QALY gains were observed in the NSEB group but the costs were also higher. The ICERs varied depending on questionnaire used, but the addition of a behavioral approach to neck-specific exercise alone was not cost-effective from a societal perspective (ICER primary outcome $127, 800 [95% confidence interval [CI], 37, 816–711, 302]). The sensitivity analyses confirmed the results. The prescription of physical activity did not result in any QALY gain and the societal costs were not lower. Conclusion: Neck-specific exercise was cost-effective from a societal perspective in the treatment of chronic WAD compared with the other exercise interventions. ICERS varied depending on health-related quality of life questionnaires used, but the addition of a behavioral approach was not cost-effective from a societal perspective. The prescription of physical activity did not result in any QALY gain and was thus not considered a relevant option.